Does home advantage without crowd exist in American football? - Szabó, D. Z.; Pérez, D. A. (arXiv e-print repository, 2021)
It is well-known that home team has an inherent advantage against visiting teams when playing team sports. One of the most obvious underlying reasons, the presence of supporting fans has mostly disappeared in major leagues with the emergence of COVID-19 pandemic. This paper investigates with the help of historical National Football League (NFL) data, how much effect spectators have on the game outcome. Our findings reveal that under no allowance of spectators the home teams' performance is substantially lower than under normal circumstances, even performing slightly worse than the visiting teams. On the other hand, when a limited amount of spectators are allowed to the game, the home teams' performance is no longer significantly different than what we observe with full stadiums. This suggests that from a psychological point of view the effect of crowd support is already induced by a fraction of regular fans.